2023
DOI: 10.3389/fimmu.2023.1029438
|View full text |Cite
|
Sign up to set email alerts
|

Role of regulation of PD-1 and PD-L1 expression in sepsis

Abstract: Long term immunosuppression is problematic during sepsis. The PD-1 and PD-L1 immune checkpoint proteins have potent immunosuppressive functions. Recent studies have revealed several features of PD-1 and PD-L1 and their roles in sepsis. Here, we summarize the overall findings of PD-1 and PD-L1 by first reviewing the biological features of PD-1 and PD-L1 and then discussing the mechanisms that control the expression of PD-1 and PD-L1. We then review the functions of PD-1 and PD-L1 in physiological settings and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 182 publications
0
14
0
Order By: Relevance
“…Therefore, exploring the immune-related aspects between sepsis and cancer represents a novel area of investigation.Our study has discovered that these 11 IIGs are closely linked with immune checkpoints, which play a crucial role in regulating the immune system, especially in tumor immune evasion 52 . This suggests the existence of tumor-like immune escape mechanisms in sepsis 53,54,55 . Previous research has shown that anti-PD-L1…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, exploring the immune-related aspects between sepsis and cancer represents a novel area of investigation.Our study has discovered that these 11 IIGs are closely linked with immune checkpoints, which play a crucial role in regulating the immune system, especially in tumor immune evasion 52 . This suggests the existence of tumor-like immune escape mechanisms in sepsis 53,54,55 . Previous research has shown that anti-PD-L1…”
Section: Discussionmentioning
confidence: 94%
“…peptides could improve survival rates in mice infected with fungi 55 , indicating that immune checkpoint pathways might play a role in immune suppression during the later stages of sepsis.Through KEGG functional enrichment analysis, we found that pathways related to cancer immunity are signi cantly enriched in sepsis, suggesting a possible intersection of immune regulation between these two diseases. Surprisingly, we also discovered that the expression of these IIGs is closely associated with the sensitivity and resistance to antitumor drugs, with the GRB2 gene showing a signi cant positive correlation with paclitaxel 56 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, post-operative monocyte PD-L1 expression increased following HKB stimulus in patients with post-operative infections, which was not evident in healthy volunteers or patients without post-operative infections. An increase in monocyte PD-L1 expression is associated with CD4 + lymphocyte inhibition via the PD-1/PD-L1 pathway suggesting a plausible mechanism ( 28 ). Elevated monocyte PD-L1 expression in critically ill patients is associated with lymphocyte anergy and increased risk of secondary infections ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in monocyte PD-L1 expression is associated with CD4 + lymphocyte inhibition via the PD-1/PD-L1 pathway suggesting a plausible mechanism ( 28 ). Elevated monocyte PD-L1 expression in critically ill patients is associated with lymphocyte anergy and increased risk of secondary infections ( 28 , 29 ). Monocyte PD-L1 is less well characterized in surgery although elevated monocyte and serum PD-L1 are associated with increased risk of infection in other inflammatory processes such as pancreatitis ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…While PD-1 blockade might enhance pathogenic microbe clearance in patients with acute and chronic infections, there is a risk that reactivation of subsets of exhausted T cells might increase tissue immunopathology, leading to immune-related adverse events. Numerous studies have linked PD-1 and its ligands to altered immune cell activity in sepsis ( 87 89 ). Ruan et al.…”
Section: Infection Immunitymentioning
confidence: 99%